2017
DOI: 10.1177/1542305017744493
|View full text |Cite
|
Sign up to set email alerts
|

Handling Stereotypes of Religious Professionals: Strategies Hospice Chaplains Use When Interacting with Patients and Families

Abstract: Stereotypes of religious professionals can create barriers for those who provide spiritual/pastoral care. Through interviews and journal entries, hospice chaplains ( n = 45) identified the following stereotypes that affected their work: chaplains as people whom others try to impress, who only talk about spiritual and religious topics, who are male, and who try to convert others. Participants reported using a variety of communication strategies to counteract stereotypes and make meaningful connections with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Authors such as Lindholm (2017), Handzo et al (2022), and Stavig et al (2022) have documented stereotypes and factual knowledge gaps that patients hold about chaplains that may affect patient desire for services and likelihood of referrals from clinical colleagues. In the context of this study, our data (Figure 4) indicated strong patient desire for outpatient chaplain care in six care scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Authors such as Lindholm (2017), Handzo et al (2022), and Stavig et al (2022) have documented stereotypes and factual knowledge gaps that patients hold about chaplains that may affect patient desire for services and likelihood of referrals from clinical colleagues. In the context of this study, our data (Figure 4) indicated strong patient desire for outpatient chaplain care in six care scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Lisäksi on havaittu, että aktiivinen, empaattinen kuunteleminen ( 21), sairaudesta puhuminen, tuki ihmissuhdeongelmissa ja elämänvaikeuksissa ovat keskeisimmät elementit ja uskonnollisen toiminnan osuus pieni. Keskustelu sairaalasielunhoitajan kanssa koetaan uskonnollissävytteiseksi, vaikkakaan kristillinen elämänkatsomus ei ole merkittävä asia kaikille sielunhoitoa toivoville (9,28).…”
Section: Sairaalasielunhoitotyön Asiantuntijuus Sairaalasielunhoitajan Näkökulmastaunclassified
“…Tavoitteet vahvistivat potilaan kokemusta oman elämän hallinnasta kokonaisvaltaisemmin, eivätkä tähdänneet pelkästään potilaan selviytymiseen kohtaamishetkessä sairaalasielunhoitajan tuella. Tulokset tukevat aikaisempia tutkimuksia, mutta painottuvat eri tavalla (5,15,17,18,20,26,28).…”
Section: Pohdintaunclassified
See 1 more Smart Citation